Créer la ville Rituels territorialisés d'inclusion des différences - GAMBA, Fiorenza (Chôra, 2022)
Our main thesis is that rituals can foster inclusion if we focus on their communality, their transformative aspect and their conviviality, which is necessary for them to be reproduced. To demonstrate this thesis, we analysed and compared eight urban rituals (in Geneva, Montreal, and Turin). The book concludes with recommendations to urban policy makers.